A proposed method to effectively combat human trafficking: lessons for the South African Criminal Justice System - Motseki, Morero (Technium Social Sciences Journal, 2022)
Human trafficking is generally understood to refer to the process through which individuals are placed or maintained in an exploitative situation for economic gain. Trafficking can occur within a country or may involve movement across borders. Women, men and children are trafficked for a range of purposes, including forced and exploitative labour in factories, farms and private households, sexual exploitation, and forced marriage. Trafficking affects all regions and most countries of the world and South Africa is no exception. This study attempt to evaluate the effectiveness of the South African Criminal Justice System (CJS) in combating human trafficking. This study was carried out utilising a qualitative approach. Forty interviews were carried out among officials deployed in the Directorate for Priority Crime Investigation (DPCI), the South African Police Service (SAPS), the Department of Home Affairs (DHA), the Department of Social Development (DSD), the Gauteng Provincial Office, as well as with the victims regarding their views and experiences on the stakeholder’s involvement in combating and investigating human trafficking. The key findings indicated that the challenges are lack of resources, capacity, budget and lack of cooperation from victims of human trafficking in supporting ongoing investigations, in adequate awareness was also a major challenge for law enforcement agencies, training, knowledge and skills to deal with human trafficking was identified to be also a big challenge for the relevant stakeholders, the findings also indicated a lack of clear strategy and response by stakeholders to successfully investigate, prosecute and incarcerate the perpetrators of human trafficking. Based on the findings, the author provided, possible recommendations such as; the South African government should develop internet regulations and policies to regulate the internet, advanced training and better education including improved awareness strategies; and collaboration with community police forums to strengthen partnerships, improve support and ensure relationship between the SAPS and the community.